Mamie Till-Mobley: Paradox and Poetics of Racialized Public Motherhood in Chinonye Chukwu’s Till (2022) - Cortina, Bernadine (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
Through an analysis of Chinonye Chukwu’s 2022 film Till, this article explores how Mamie Till-Mobley’s motherhood is cinematically represented. Focusing on director Chinonye Chukwu’s matrifocal lens, it analyzes racialized public motherhood and its painful containment of mothers within the institution of motherhood alongside radical and life-affirming possibilities for mothering in the wake of Black maternal necropolitics. This article looks at how racialized public motherhood allows mothers to continue the work of mothering and affirming their children’s humanity and the value of their lives even when all that remains of them is their dead bodies. It explores the multiple, often difficult strategies Mamie Till-Mobley employed in the fight to lovingly shape the meaning of her son’s life and death that have profoundly changed the course of American history. In this way, I connect this historical example of racialized public motherhood in Mamie’s practice to its contemporary, local, and intersectional implications. This article highlights the long line of Black maternal activists that have followed Mamie, as Black children are still dying from police violence and other forms of anti-Blackness, and closes with reflections on the cost to Black mothers and the tensions around Black women’s subjectivity. It aims to show how continued racial violence in the United States necessarily connects the struggle of mothers across temporalities.